PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS POWTOON MATERI KONVERSI SATUAN PANJANG MUATAN MATEMATIKA KELAS III SD - Saputra, Agus; Cahyati, Leni; Khairita, Martiya Nurni (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The rapid development of science and technology affects all aspects of human life. Aspects in the field of education are one of the recipients of the impact of science and technology development. Developments in the world of education are very prominent in the digital world, especially aspects of learning media. One of the mathematics learning media that can be developed is powtoon-based animated video media. This study aims to produce products that meet valid, practical and effective criteria. The development model used is the ADDIE model with 5 stages. In this study the researchers took 17 students in class III SD Negeri 04 Sungai Rumbai as test subjects. Data was collected using validation sheets, practicality and effectiveness sheets. The validation sheet is filled in by the validator, namely a lecturer at Dharmas Indonesia University. The results of the material validity sheet obtained a percentage of 94.3%, categorized as very valid. The results of the construct/media validity sheet obtained 80% results categorized as valid, the media validity sheet obtained 95% results categorized as very valid. The lesson plan validity sheet obtained 94% results which were categorized as very valid and the question validity sheet obtained 97% results which were categorized as very valid. The results of the teacher's response practicality sheet obtained 88.9% results categorized as very practical, student response practicality sheets obtained 95% results categorized as very practical. Results Analysis of effectiveness data obtained results of 88% for students who completed and 12% for students who did not complete, so that powtoon-based animated video media was categorized as valid, practical and effective to use.